PREPARATION OF SULPHONATED PVA-TMSP MEMBRANES FOR DIRECT METHANOL FUEL CELL - , Haryadi , Riniati , Sofiatun Anisa , Ayu Utami ([Yogyakarta] : Chemistry Departement Universitas Gadjah Mada, 2010)
Novel preparation and characterization of sulphonated PVA-TMSP composite membranes for Direct Methanol Fuel Cell (DMFC) application have been investigated. Preparation of sulphonated PVA TMSP membrane was conducted by crosslinking step between PVA solution and TMSP (trimethoxysilyl propanthiol) by sol-gel method at 65 &#8304